Hubungan Antara Keterampilan Komunikasi Terhadap Sikap Siswa Dalam Pembelajaran Fisika Di SMA Negeri 1 Dolok Kelas X - Irma Suryani Siregar; Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar (Universitas Gara Nusantara Padangsidimpuan, 2025)
Physics learning is often considered difficult and boring by students, which impacts their low learning motivation and active engagement in class. Students' communication skills and attitudes are important factors that can influence the success of physics learning. This study aims to analyze the relationship between students' communication skills and their attitudes toward physics learning at SMA Negeri 1 Dolok Grade X. The research uses a quantitative approach with a correlational design. The research population consists of all Grade X students at SMA Negeri 1 Dolok with a saturated sample of 30 students. The research instruments include a communication skills questionnaire (30 items) and an attitude toward physics learning questionnaire (24 items) using a Likert scale. Data were analyzed using Pearson Product Moment correlation test with SPSS 17. The conclusion of this study is that there is a significant and strong relationship between students' communication skills and their attitudes toward physics learning. Improvement in communication skills can contribute to the formation of positive attitudes among students in physics learning. This can be seen from the R Square value of 0.630, indicating that communication skills contribute 63% to students' attitudes in physics learning.